Superhydrophobic Silica Ultrasonic Coating Based on Sinabung Volcanic Ash as Anti-Corrosion of Ferrous Metal Materials - Christin T. N. Simanjuntak; Dea Gracella Siagian; Kristian Adinata Pratama Simatupang; Dafit Ericson Sihotang; Lisnawaty Simatupang (Jurnal Ilmiah Berkala Sains dan Terapan Kimia, 2024)
This research aims to measure the superhydrophobic performance of silica and the effect of sonification (ultrasonically dip coating) on the effectiveness of coatings on iron metal in corrosive solutions of 15% HCl (v/v) and 3.5% NaCl (w/v). This research utilizes ultrasonic waves to disperse superhydrophobic silica and paint into a homogeneous mixture and applies this mixture as a protective coating material on the surface of iron metal with the help of ultrasonic waves with the aim of increasing its ability to inhibit iron metal corrosion. The main material used in this research is Sinabung volcanic ash-based silica which was synthesized using the sol-gel method. The addition of superhydrophobic silica material to the paint was carried out by dispersing (0; 0.6; 1.2; 1.8) g with 10 mL of paint using an ultrasonic homogenizer for 15 minutes. The corrosion test was carried out by immersing the sample in a corrosive solution for 96 hours. As a result, sonification (ultrasonically dip coating) and variation in superhydrophobic silica composition are shown to affect the corrosion resistance of ultrasonic superhydrophobic silica coatings on iron surfaces. As a result of the lowest corrosion rates in each solution, 64.51 mpy (HCl 15%) and 2.63 mpy (NaCl 3.5%) were achieved. Invariant superhydrophobic silica compositions of 1.8:10g/mL showed the highest inhibitory effectiveness of 83.40% (HCl 15%) and 93.75% (NaCl 3.5%).